Phylogeography of Coastal Turtle Populations (Zoological Archives: An International Journal, 2022)
Coastal sea turtle populations present a paradox of spatial ecology: females exhibit extreme natal philopatry -- returning to their birth beach to nest -- while males and juveniles undertake extensive trans-oceanic migrations that should, in principle, generate high gene flow among populations separated by thousands of kilometres of open ocean. Understanding how these contrasting dispersal tendencies produce the observed population genetic structure is essential for defining the management units that underpin effective sea turtle conservation. This study presents the most comprehensive phylogeographic analysis of the loggerhead turtle (Caretta caretta) and green turtle (Chelonia mydas) yet conducted for the Atlantic-Mediterranean basin, combining mitochondrial control region sequencing (1,247 individuals; 21 nesting populations) with nuclear microsatellite genotyping (847 individuals; 8 microsatellite loci) and stable isotope mixing models from epibiont assemblages to quantify foraging ground usage by population. Mitochondrial haplotype structure showed strong population differentiation (overall FST = 0.284 +- 0.048 for loggerheads; 0.347 +- 0.054 for green turtles) consistent with female natal philopatry driving population structure at the nesting beach scale. Nuclear microsatellite FST was substantially lower (0.084 +- 0.018 for loggerheads) reflecting male-mediated gene flow across nesting populations. Bayesian mixed stock analysis confirmed that the Spanish Mediterranean foraging aggregation draws from 4.7 +- 1.4 Atlantic and Mediterranean source populations -- identifying a management unit mismatch where foraging ground regulation affects multiple nesting beach management units simultaneously.